The Effect of Smoking Habit on Apical Status of Adequate Endodontically Treated Teeth with and Without Periodontal Involvement - Mahmood AA; AbdulAzeez AR; Hussein HM (Dove Medical Press, 2019)
Athraa A Mahmood,1 Ali R AbdulAzeez,2 Hashim M Hussein3 1Department of Periodontology, College of Dentistry, Mustansiriyah University, Baghdad, Iraq; 2Department of Periodontology, College of Dentistry, Uruk University, Baghdad, Iraq; 3Department of Dentistry, Al-Raﬁdain University-College, Baghdad, IraqCorrespondence: Hashim M HusseinDepartment of Dentistry, Al-Raﬁdain University-College, Palestine Street, P.O., Box 46036, Baghdad, IraqTel +964 780 710 1071Email hashimmueenhussein@gmail.comBackground: The possible connection between apical periodontitis (AP), periodontal disease (PD) and the bad habit of smoking is among the most interesting aspects faced by the dental scientific community. The aim of this study was to pinpoint the effect of smoking on the status of the apical region, in properly root-filled teeth with and without periodontal involvement of Iraqi males.Materials and methods: Total number of 75 patients were chosen, divided into 3 groups of 25’s, teeth were subdivided into 6 subgroups (G-a: Light smokers without Periodontal involvement, G-b: Heavy smokers without Periodontal involvement, G-c: Non-smokers without Periodontal involvement, G-d: Light smokers with Periodontal involvement, G-e: Heavy smokers with Periodontal involvement, G-f: Non-smokers with Periodontal involvement), examination involved: clinical periodontal parameters, coronal restoration fitness. Panoramic and periapical radiographs were used to judge the quality of periodontal tissue in the apical region (AP) of root canal treated teeth.Results: Among all the examined teeth (1859), only (89) were found with fitted both coronal and endodontic restorations. Rates of AP were: (G-a: 11.1%, G-b: 25%, G-c: 0%, G-d: 18.8%, G-e: 35.7%, G-f: 4.8%). Statistically, in related to the AP, there was a highly significant difference between heavy smokers’ groups (G-b, G-e). Moreover, heavy smokers with PD (G-e) showed a significant difference with light smokers without PD (G-a) and non-smokers without PD (G-c), also, there was a significant difference between heavy smokers without PD (G-b) and non-smokers with PD (G-f). While, there was a non-significant difference relationship between non–smokers’ groups (G-c, G-f), and light smokers’ groups (G-a, G-d).Conclusion: There is a noticeable negative effect of smoking on the severity and prognosis of AP and this negative effect worsens when it is accompanied by lateral periodontitis.Keywords: smoking, apical periodontitis, root canal therapy, periapical index